Selected topics of parameterization of circuit models of 25 kV 50 Hz traction supply networks with converter substations - Žižlavský, Petr; Novák, Jaroslav; Hebelka, Vlastimil (International Academy of Science, Engineering, and Technology (International ASET), 2024)
Selected steps in determining peripheral structures and their parameters during simulating modeling of 25 kV 50 Hz traction networks with continuous power supply by inverter power stations are presented in the article. The purpose is to find a suitable methodology for creating the structure and parameterization of circuit models for pre-project preparation and parameterization of output characteristics of inverters in substations and parameterization of distance short-circuit protections. In particular, an analysis of the impact of respecting the capacities of the traction circuit is presented.
Vybrané problémy parametrizace obvodových modelů trakčních sítí 25 kV 50 Hz s měničovými napájecími stanicemi
Keywords: converter power supply station; track parametrization; traction power network 25 kV 50 Hz; distance protection; měničová napájecí stanice; parametrizace trati; trakční napájecí síť 25 kV 50 Hz; distanční ochrana